Processo de desenvolvimento de produtos Lean e Green: um modelo unificado - Guedes, Bruno Turmina (2018)
The product development comprises a set of operations that aims to convert an idea and/or market opportunity into a product that meets the requirements of the final consumer. In addition, the quest for quality, reduction of developing time e waste, allied to the environmental responsibility/awareness, have been pushing the New Product Development (NPD) to cover lean e green aspects, LPD e GPD. That is, through lean operations, design green products. Therefore, this study attempts to a unified model that talk to both perspectives. In the first step, it was gathered the main characteristics of both dimensions in 8 dimensions, presenting a lean-green unified framework. From this, using an evaluation tool composed of 55 questions, a synergy and a congruence of these elements were evaluated. As a result, the unified framework can hyerarchized NPDs, with a four-level maturity scale. In the second step, the use of two MCDM tools: AHP and Fuzzy-TOPSIS, each lean-green enabler of a universe of 14 enablers, that are characteristics to organizational dimension. That is, the AHP defines a reference relative to the characteristics inherent to SMEs. An expansion of the TOPSIS technique was applied, when the values of each alternative are not visible. Thus, a structured interview was organized, composed of 224 evaluations, made to the NPD stakeholders of the SMEs. Descending in this ranking, based on the best results and / or green of an SME, while the ones that perform better are the deficiencies in product development processes and operations that are not exploited by SMEs. The diagnosis was made in the three companies of the Brazilian market, considering NPD operations, being useful to define the points that are improved in each context. Thus, the unified model is composed of maturity evaluation tools, as well as multicriteria for best practices hierarchy and greener NPD processes of SMEs.